Lack of association between genetic variability and multiple pain-related outcomes in a large cohort of patients with advanced cancer: the European Pharmacogenetic Opioid Study (EPOS). Issue 4 (27th September 2012) - Fladvad, Torill; Fayers, Peter; Skorpen, Frank; Kaasa, Stein; Klepstad, Pål
Abstract : Objective: This study examined whether the choice of pain-related outcome to represent opioid efficacy influenced findings in a genetic association study. Data from the European Pharmacogenetic Opioid Study, which used opioid dose as the outcome, were analysed in respect of six alternative outcomes: average pain intensity, pain right now, worst pain intensity, pain at its least, pain relief and pain interference. Design: Cancer pain patients using an opioid for moderate or severe pain were included. The pain outcomes were obtained using the Brief Pain Inventory. Genetic variation was analysed for 112 single nucleotide polymorphisms (SNPs) in 25 candidate genes relevant for opioid efficacy. The patients were randomly divided into a development and a validation sample and linear regression was used to compare the equality of means in the six outcomes. The influence of non-genetic factors was controlled for, the regression analyses were stratified by country, and the results were corrected for multiple testing. Results: 2201 cancer pain patients were included. Their mean age was 62.4 years and mean average pain was 3.5. None of the examined SNPs exceeded p values corrected for multiple testing for any of the outcomes. Conclusions: None of the outcomes were associated with variation in the selected SNPs, as previously shown for opioid dose. Thus, we observed that findings related to associations between genetic variability and opioid efficacy were consistent for several alternative outcomes.